ANALYSIS OF THE INFLUENCE OF THE PRODUCTION COST BUDGET AND CASH BUDGET ON THE COMPANY'S PLANNING AND CONTROL BUDGET: Indriani Eka Diyah Ningsih*, Nia Saniah, Aryana Nurwahidah, Elga Anggun Puspita, Griselda Amelia - Indriani Eka Diyah Ningsih; Nia Saniah; Aryana Nurwahidah; Elga Anggun Puspita; Griselda Amelia (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2024)
This research aims to analyze the influence of the production cost budget and cash budget on the planning and control budget of trading companies. The method used is qualitative with a literature study that utilizes literature from previous research results. The research results show that a well-prepared production cost budget provides an accurate picture of the required production costs, helps in planning and controlling company activities, as well as monitoring and evaluating company performance. A detailed production cost budget allows a company to compare actual costs with a predetermined budget, so that control measures can be taken to reduce costs or take necessary corrective actions. The process of preparing a cash budget involves several important steps, such as preparing estimates of revenues and expenditures based on operational plans, as well as preparing estimates of funding needs from external sources. Preparing a good cash budget helps companies identify potential financial problems before they occur, allows for better long-term financial planning, and helps in making strategic decisions. In conclusion, both the production cost budget and the cash budget play an important role in the company's financial planning and control, ensuring financial balance and smooth company operations. A thorough planning process and careful analysis are needed to achieve optimal benefits from preparing this budget.